Manure management practices applied to a seven‐course rotation on a sandy soil: effects on nitrate leaching. (21st January 2013) - Shepherd, M.; Newell‐Price, P.
Abstract This experiment tested whether it was possible to incorporate broiler litter (BL) or cattle farmyard manure (FYM) into a 7‐yr arable rotation on a sandy soil without causing an increase in nitrate‐nitrogen (NO3‐N) leaching. Four manure treatments (with adjusted fertilizer inputs), varying in frequency and timing of application, were imposed on the rotation and compared with a control that received inorganic fertilizer according to recommended rates. Over seven winters, the annual average NO3‐N leached from the inorganic fertilizer treatment (control) was 39 kg/ha in 183 mm drainage. Total manure N loadings over the period of the experiment ranged between 557 and 1719 kg/ha (80–246 kg/ha/yr) for the four treatments. Three of the four manure treatments significantly increased NO3‐N leaching over the rotation (P < 0.001). Annual applications of FYM (1719 kg/ha manure N or 246 kg/ha/yr) increased NO3‐N leaching by 39%. We hypothesize that this was due to increased mineralization of the organic N accumulating from repeated FYM applications. BL applied each year (1526 kg/ha manure N or 218 kg N/ha/yr) increased NO3‐N leaching by 52% above the control; BL applied 5 of 7 yr (972 kg/ha manure N or 139 kg N/ha/yr on average) and including inadvisable autumn applications increased leaching by 50%. BL applied in late winter or early spring every 2–3 yr (557 kg/ha manure N or 80 kg N/ha/yr on average) resulted in NO3‐N leaching similar to the control. This suggests that to avoid additional NO3‐N leaching from manure use in an arable rotation, manure should not be applied every year and autumn applications should be avoided; there are real challenges where manure is used on an annual basis.